Application of array-comparative genomic hybridization in tetralogy of Fallot. Issue 49 (December 2016) - Liu, Lin; Wang, Hong-Dan; Cui, Cun-Ying; Wu, Dong; Li, Tao; Fan, Tai-Bing; Peng, Bang-Tian; Zhang, Lian-Zhong; Wang, Cheng-Zeng
Abstract : Abstract: To explore the underlying pathogenesis and provide references for genetic counseling and prenatal gene diagnosis, we analyzed the chromosome karyotypes and genome-wide copy number variations (CNVs) in 86 patients with tetralogy of Fallot (TOF) by G-banding karyotype analysis and array-comparative genomic hybridization (aCGH), respectively. And then quantitative polymerase chain reaction was used to validate these candidate CNVs. Based on their different properties, CNVs were categorized into benign CNVs, suspiciously pathogenic CNVs, and indefinite CNVs. Data analysis was based on public databases such as UCSC, DECIPHER, DGV, ISCA, and OMIM. The karyotype was normal in all the 86 patients with TOF. CNVs were detected in 11 patients by aCGH and quantitative polymerase chain reaction. Patient no. 0001, 0010, and 0029 had 2.52-Mb deletion in the chromosome 22q11.21 region; patient no. 0008 had both 595- and 428-kb duplications, respectively, in 12p12.3p12.2 and 14q23.2q23.3 regions; patient no. 0009 had 1.46-Mb duplication in the 1q21.1q21.2 region; patient no. 0016 had 513-kb duplication in the 1q42.13 region; patient no. 0024 had 292-kb duplication in the 16q11.2 region; patient no. 0026 had 270-kb duplication in the 16q24.1 region; patient no. 0028 had 222-kb deletion in the 7q31.1 region; patient no. 0033 had 1.73-Mb duplication in the 17q12 region; and patient no. 0061 had 5.79-Mb deletion in the 1p36.33p36.31 region. aCGH can accurately detect CNVs in the patients with TOF. This is conducive to genetic counseling and prenatal diagnosis for TOF and provides a new clue and theoretical basis for exploring the pathogenesis of congenital heart disease. Abstract : Supplemental Digital Content is available in the text